A CALORIMETRIC STUDY OF THE ULTRASOUND-STIMULATED HYDROLYSIS OF SOLVENTLESS TEOS-WATER MIXTURES - Donatti, D. A.; Vollet, D. R. (Kluwer Academic Publ, 1995)
The kinetics of ultrasound-stimulated and HCl-catalyzed hydrolysis of solventless TEOS-water mixtures was studied as a function of temperature ranging from 10 degrees C up to 65 degrees C by means of flux calorimetry measurements. A specially designed device was utilized for this purpose. The exothermic peak arising few minutes after sonication began has been attributed mainly to the hydrolysis reaction. The overall hydrolysis process, which was measured through the irradiation time up to the hydrolysis peak, was found to be thermally activated, with an apparent activation energy Delta E = 36.4 kJ/mol. The alcohol produced at the early hydrolysis due to sonication seems to further enhance the reaction, via a parallel autocatalytic path, which is controlled by a faster pseudo second order rate constant (k'). Our modeling yielded k' = 6.3 x 10(-2) M(-1) min(-1) at 20 degrees C, which is in a reasonable agreement with the literature, and an activation energy Delta E = 40.4 kJ/mol for the specific process of hydrolysis in presence of alcohol.
Keywords: HYDROLYSIS; TEOS; SONICATION; CALORIMETRY; RATE CONSTANTS